Pt‐WOx/C Catalysts for α, β‐Unsaturated Aldehydes Hydrogenation: An NMR Study of the Effect of the Reactant Adsorption on Activity and Selectivity. Issue 40 (21st October 2022) - Stucchi, Marta; Vasile, Francesca; Cattaneo, Stefano; Vomeri, Alessandro; Hungria, Ana B.; Prati, Laura
Abstract: The selective hydrogenation of α, β‐unsaturated aldehydes is an ideal case for studying the structure‐activity relationships in heterogeneous catalysis. In particular, cinnamaldehyde can be used as probe molecule for revealing the competition between hydrogenation of C=C and C=O bond. Here, we investigated the effect of the modification of some Pt supported on carbon catalysts by WOx species in cinnamaldehyde hydrogenation, as WOx species are reported to increase the adsorption and activation of the C=O group of α, β‐unsaturated aldehydes. Classical techniques used for correlating the catalyst activity and the selectivity to the characteristic of the materials (XRD, HAADF‐STEM, XEDS mapping and XPS) have been coupled with NMR relaxometry, as innovative application, to disclose how the molecule approaches the catalyst surface. This indeed constitutes a crucial aspect that rule the catalytic activity. Therefore, an innovative, holistic approach has been used to consider the whole catalytic system. Abstract : Pt/C catalysts have been modified by WOx using different approaches. The changed activity and selectivity towards cinnamaldehyde hydrogenation were correlated to the characteristic of the materials by classical techniques, and coupled with NMR relaxometry, which allowed disclosing the strength of interaction of the molecule with the catalyst surface.